Nuffield economics and business : Teacher's Resources - Longman Group (Singapore : Longman, 1995)
This project integrates economics and business studies at AS and A level. It combines a systematic and analytical approach to business with the applications of a streamlined body of economic theory. An investigative approach is used throughout the resources in order to encourage students to take responsibility for their own learning. Real world problems are examined using the critical insights of both subjects to create an active understanding of the important concepts. The student's book covers everything required for the AS syllabus and for the core of the A level courses. Case study material shows how business and economic theories are applied in the real world. Questions are used throughout the text to help students test their understanding of the issues rasied.
Keywords: Business; Economics